Towards an Ecological Philosophy of Education: Eco-Education Against Cartesian Nature - Güler, Oya (My University, 2025)
This study examines how the Cartesian thought structure in modern education affects the relationship between humans and nature, emphasizing the need for an ecological educational philosophy. Cartesian thought has fostered a human-centered perspective that perceives nature as a mechanical entity, exacerbating environmental challenges. In contrast, ecological education aims to cultivate individuals' sensitivity to environmental issues and foster ethical responsibility by recognizing the essential relationship between humans and the natural world. By analyzing these effects, this research highlights that ecological education enhances environmental awareness, supports the adoption of sustainable lifestyles, and encourages harmonious interactions with nature. Restructuring education systems with an ecological paradigm will equip individuals with the knowledge necessary to comprehend environmental challenges and contribute to sustainable practices and conservation efforts.
Keywords: Environmental Awareness; Sustainability; Nature; Ecological Education; Cartesian Thought; Philosophy Of Education.